Réception des campagnes de communication de santé publique et efficacité des messages suscitant de la peur - Didier Courbet (Communication)
The article firstly addresses the critical state of research on the influence of public health communication campaigns that attempt to modify disastrous attitudes towards the health of individuals by appealing to fear. It goes on to explain an experimental study of the role played by fear after repeated exposure to a message. The results show that the strong representations of danger are efficient in the intention to stop smoking only after exposure to the message is repeated several times. Surprisingly, the receivers who feel the most vulnerable to cancer are those who do not have the intention of quitting smoking. The subjects who feel least vulnerable have a strong intention of stopping. The results are discussed within the theoretical framework of biased treatment of information